The Impact of Implementing International Financial Reporting Standards (IFRS) on the Efficiency and Effectiveness of Internal Auditing in Financial Institutions - Aqeel Raham Hassoon (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Financial reporting is essential for providing transparent and comparable financial information to stakeholders, encouraging the adoption of global accounting standards. Specific Background: International Financial Reporting Standards (IFRS) provide a unified framework to standardize financial reporting practices across institutions. Knowledge Gap: Empirical evidence on IFRS adoption and financial reporting quality in developing economies, particularly Iraqi financial institutions, remains limited. Aims: This study examines IFRS adoption and its relationship with financial reporting quality while considering internal control systems. Results: Data from 512 financial professionals analyzed using PLS-SEM show that perceived benefits, ease of adoption, and government support encourage IFRS implementation, while legal enforcement plays a smaller role. IFRS adoption is associated with improved clarity, comparability, and timeliness of financial reports. Novelty: The study presents empirical evidence from Iraqi financial institutions and evaluates internal control systems within this relationship. Implications: The findings provide guidance for policymakers to support IFRS implementation and promote transparent financial reporting practices. Highlights:• IFRS Adoption in Iraqi Financial Institutions Is Primarily Motivated by Perceived Benefits, Ease of Implementation, and Government Support.• Financial Statements Prepared Under IFRS Demonstrate Higher Levels of Accuracy, Comparability, Clarity, and Reporting Timeliness.• Internal Control Systems Show Limited Moderating Contribution in the Relationship Between IFRS Adoption and Reporting Quality. Keywords: IFRS Adoption, Financial Reporting Quality, Internal Control System, Financial Institutions, Iraq